2024
DOI: 10.3389/frhs.2024.1306461
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity on prescription for children with obesity: a focus group study exploring experiences in paediatric healthcare

Charlotte Boman,
Susanne Bernhardsson,
Stefan Lundqvist
et al.

Abstract: BackgroundInsufficient physical activity is a growing public health concern and is closely linked to obesity in both adults and children. Swedish physical activity on prescription (PAP) is effective in increasing physical activity levels in adults, but knowledge about how PAP is used in paediatric healthcare is lacking. Therefore, this study aimed to explore experiences of working with PAP for children with obesity amongst paediatric staff and managers.MethodsSeven focus group discussions with 26 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This means an expanded collaboration around the PAP model, providing children with a supportive environment in the form of a network of adults—both medical and educational professionals in school and the family. Also in pediatric healthcare, it is shown that collaboration between different professionals and physical activity organizers is essential to respond to children's needs and promoting effective use of PAP ( 10 ). Establishing lifelong learning and promoting changes in physical activity patterns is a multifaceted effort.…”
Section: Introductionmentioning
confidence: 99%
“…This means an expanded collaboration around the PAP model, providing children with a supportive environment in the form of a network of adults—both medical and educational professionals in school and the family. Also in pediatric healthcare, it is shown that collaboration between different professionals and physical activity organizers is essential to respond to children's needs and promoting effective use of PAP ( 10 ). Establishing lifelong learning and promoting changes in physical activity patterns is a multifaceted effort.…”
Section: Introductionmentioning
confidence: 99%